The Effect of Manipulating Training Demands and Consequences on Experiences of Pressure in Elite Netball. Issue 4 (2nd October 2017) - Stoker, Mike; Maynard, Ian; Butt, Joanne; Hays, Kate; Lindsay, Pete; Norenberg, Danielle Adams
Abstract : Testing the efficacy of a pressure training framework (Stoker, Lindsay, Butt, Bawden, & Maynard, 2016 ), the present study investigated whether manipulating training demands and consequences altered experiences of pressure. Elite Netballers ( M age = 26.14 years) performed a Netball exercise in a randomized, within-subject design with four conditions: a control, consequences, demands, and demands plus consequences condition. Compared with the control, self-reported pressure was significantly higher in the consequences and demands plus consequences condition but not in the demands condition. The findings provide mixed support for manipulating demands and strong support for manipulating consequences as a means for producing pressure.